Efficient Mn(II) removal mechanism by Serratia marcescens QZB-1 at high manganese concentration - Huang, Xuejiao; Nong, Xiaofang; Liang, Kang; Chen, Pengling; Zhao, Yi; Jiang, Daihua; Xiong, Jianhua (Frontiers in Microbiology, 2023)
Manganese (Mn(II)) pollution has recently increased and requires efficient remediation. In this study, Serratia marcescens QZB-1, isolated from acidic red soil, exhibited high tolerance against Mn(II) (up to 364 mM). Strain QZB-1 removed a total of 98.4% of 18 mM Mn(II), with an adsorption rate of 71.4% and oxidation rate of 28.6% after incubation for 48 h. The strain synthesized more protein (PN) to absorb Mn(II) when stimulated with Mn(II). The pH value of the cultural medium continuously increased during the Mn(II) removal process. The product crystal composition (mainly MnO2 and MnCO3), Mn-O functional group, and element-level fluctuations confirmed Mn oxidation. Overall, strain QZB-1 efficiently removed high concentration of Mn(II) mainly via adsorption and showed great potential for manganese wastewater removal.